2013
DOI: 10.1007/s00586-013-2999-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of posterior facet versus pedicle screw fixation of circumferential fusion: a cohort study

Abstract: Purpose To compare single-level circumferential spinal fusion using pedicle (n = 27) versus low-profile minimally invasive facet screw (n = 35) posterior instrumentation. Method A prospective two-arm cohort study with 5-year outcomes as follow-up was conducted. Assessment included back and leg pain, pain drawing, Oswestry disability index (ODI), pain medication usage, self-assessment of procedure success, and [1-year postoperative lumbar magnetic resonance imaging. Results Significantly less operative time, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…34 In the present study, postoperative MRI found the T2 signal intensity ratio of the multifidus muscles to psoas control muscle to be substantially increased relative to the preoperative ratio. Within the author's region, some spine surgeons never remove instrumentation, whereas other do so routinely.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…34 In the present study, postoperative MRI found the T2 signal intensity ratio of the multifidus muscles to psoas control muscle to be substantially increased relative to the preoperative ratio. Within the author's region, some spine surgeons never remove instrumentation, whereas other do so routinely.…”
Section: Discussionsupporting
confidence: 44%
“…In this study of 2level fusion patients, the injection most commonly was made at L5 and S1 but, in a few patients, up to 6 pedicle screwheads were injected. 34,51 A post hoc power analysis was performed to determine the number of patients that would have to be studied to show a difference in VAS low back pain and ODI. Three patients did not improve with the diagnostic portion of the injection, and their instrumentation was retained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the duration of post-operation narcotic use, a number of studies reported results reflecting other post-operation narcotic uses (Additional file 5 : Other results of post-operation narcotic usage). A total of ten studies [ 18 , 21 , 22 , 43 , 44 , 46 , 48 51 ] directly compared the MIS and OS procedures, three studies [ 25 , 33 , 52 ] only focused on MIS and five studies only used OS [ 26 , 28 , 38 , 45 , 47 ]. The proportion of patients who used narcotics for pain control, at different follow-up intervals were frequently described, but the definition of narcotics was not clearly described.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed lower incidence of surgical trauma with translaminar facet fixation compared to transpedicular stabilization, yet the data about biomechanical recovery of the operated spinal region and the timescales of reliable bone block formation are rather contradictory [13][14][15].…”
mentioning
confidence: 99%